Assessment of Creativity Level of Secondary School Students in Moro Local Government Area of Kwara State, Nigeria - Tunde, Saadu Usman (Mediterranean Journal of Social Sciences, 2012)
This study examined the creativity level of Upper Basic Secondary School Students in Moro LocalGovernment Area of Kwara State. Descriptive survey was adopted for this study. Simple random samplingtechnique was used to select seven ( 7) Universal Basic Education (UBE) schools out 21 UBE schools in MoroLocal Government Area of Kwara State. Also, thirty (30) students were randomly selected across 7 schoolsand the total numbers of 210 students were selected. Creativity assessment scale, adopted fromAnimasahun (2007) was used to measure the creativity level of the students. Two research questions werepostulated and answered with percentage. The findings of the study revealed that the creativity ofUniversal Basic Education students was low and that male students are more creative than femalestudents. On the basis of these findings, the following recommendations were made among others thatteachers should always use methods that would promote creativity among students. Similarly divergentthinking should be promoted among students by encouraging open-ended questions. Conducive learningenvironment should be provided for the students so as to enhance creative potentials.